Radioimmunotherapy Combined with Maintenance Anti-CD20 Antibody May Trigger Long-Term Protective T Cell Immunity in Follicular Lymphoma Patients. (26th November 2013) - Buchegger, Franz; Larson, Steven M.; Mach, Jean-Pierre; Chalandon, Yves; Dietrich, Pierre-Yves; Cairoli, Anne; Prior, John O.; Romero, Pedro; Speiser, Daniel E.
Abstract : Growing evidence suggests that the patient's immune response may play a major role in the long-term efficacy of antibody therapies of follicular lymphoma (FL). Particular long-lasting recurrence free survivals have been observed after first line, single agent rituximab or after radioimmunotherapy (RIT). Rituximab maintenance, furthermore, has a major efficacy in prolonging recurrence free survival after chemotherapy. On the other hand, RIT as a single step treatment showed a remarkable capacity to induce complete and partial remissions when applied in recurrence and as initial treatment of FL or given for consolidation. These clinical results strongly suggest that RIT combined with rituximab maintenance could stabilize the high percentages of patients with CR and PR induced by RIT. While the precise mechanisms of the long-term efficacy of these 2 treatments are not elucidated, different observations suggest that the patient's T cell immune response could be decisive. With this review, we discuss the potential role of the patient's immune system under rituximab and RIT and argue that the T cell immunity might be particularly promoted when combining the 2 antibody treatments in the early therapy of FL.